A review on analytical methods of petroleum hydrocarbons in water and sediment of aquatic systems. Issue 1 (January 2021) - Yue, Zongkai; Shi, Qirang; Ai, Jia; Peng, Shitao; Miao, Xinyu; Wang, Zhiyong
Abstract: In this paper, the research progress on the extraction and analysis methods of petroleum hydrocarbon in water and sediment were reviewed. The principle, application scope, advantages, disadvantages and applications of various extraction methods and determination methods are summarized systematically. At present, liquid-liquid extraction is the most commonly used method to extract petroleum hydrocarbons (PHCs) in water samples, while Soxhlet extraction and ultrasonic extraction are the most commonly used methods to extract PHCs in sediment samples. Gas chromatography is the main development direction to determine the concentration of specific components of PHCs.